Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.fertnstert.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

HOXA-10 and E-cadherin expression in the endometrium of women with recurrent implantation failure and recurrent miscarriage

Abstract: There is a positive correlation between levels of HOXA-10 and E-cadherin expression in the endometrium, both of which are significantly reduced in women with RIF and RM compared with fertile control women. The findings suggest a potential role of HOXA-10 and E-cadherin in the implantation processes and altered expression in women with reproductive failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 46 publications
(58 reference statements)
1
43
0
Order By: Relevance
“…Peak HOXA10 and HOXA11 expressions are first observed during the window of endometrial receptivity. Decreased HOXA10 expression leads to a decreased implantation rate; furthermore, HOXA10 expression is significantly low in cases of recurrent miscarriage and recurrent implantation failure [15]. Recently, it was reported that BPA exposure results in downregulation of HOXA10 [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peak HOXA10 and HOXA11 expressions are first observed during the window of endometrial receptivity. Decreased HOXA10 expression leads to a decreased implantation rate; furthermore, HOXA10 expression is significantly low in cases of recurrent miscarriage and recurrent implantation failure [15]. Recently, it was reported that BPA exposure results in downregulation of HOXA10 [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LIF deficiency results in the loss of embryos during early pregnancy in murine [12,13,14]. A low expression of HOXA10 mRNA results in a decreased implantation rate [15]; whereas, downregulation of MUC1 mRNA and its protein prior to implantation allows the embryo to attach to the maternal uterus [5,16,17]. Furthermore, LIF and MUC1 were shown to enhance the calcium ion level in in vitro experiments [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In mice, expression of E-cadherin in the uterus was reported to increase under progesterone influence [41]. The importance of E-cadherin in implantation was evidenced from the observed low E-cadherin level in infertile women who suffer from recurrent implantation failure and miscarriages [42]. In the meantime, expression of integrin avb3 in early pregnancy period was also found to be reduced following high dose quercetin administration.…”
Section: Discussionmentioning
confidence: 96%
“…7 Since then, integrin, 8 glycodelin, 9 mucin 1, 10 leukemia inhibitory factor (LIF), 8,11 and HOXA-10 transcription factor 12 have also been described as potential endometrial biomarkers. Pinopodes were reported as a biomarker to assess endometrial receptivity since their putative expression coincides with the window of implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Pinopodes were reported as a biomarker to assess endometrial receptivity since their putative expression coincides with the window of implantation. 7 Since then, integrin, 8 glycodelin, 9 mucin 1, 10 leukemia inhibitory factor (LIF), 8,11 and HOXA-10 transcription factor 12 have also been described as potential endometrial biomarkers. Nevertheless, only a few markers are currently utilized in clinical practice due to the conflicting results and technical difficulties for their use on patients.…”
Section: Introductionmentioning
confidence: 99%